Presequence translocase-associated motor subunits of the mitochondrial protein import apparatus are dual-targeted to mitochondria and plastids - Gill-Hille, Mabel; Wang, Andre; Murcha, Monika W. (Frontiers in Plant Science, 2022)
The import and assembly of most of the mitochondrial proteome is regulated by protein translocases located within the mitochondrial membranes. The Presequence Translocase-Associated Motor (PAM) complex powers the translocation of proteins across the inner membrane and consists of Hsp70, the J-domain containing co-chaperones, Pam16 and Pam18, and their associated proteins Tim15 and Mge1. In Arabidopsis, multiple orthologues of Pam16, Pam18, Tim15 and Mge1 have been identified and a mitochondrial localization has been confirmed for most. As the localization of Pam18-1 has yet to be determined and a plastid localization has been observed for homologues of Tim15 and Mge1, we carried out a comprehensive targeting analysis of all PAM complex orthologues using multiple in vitro and in vivo methods. We found that, Pam16 was exclusively targeted to the mitochondria, but Pam18 orthologues could be targeted to both the mitochondria and plastids, as observed for the PAM complex interacting partner proteins Tim15 and Mge1.